2022
DOI: 10.1021/jacs.1c12798
|View full text |Cite
|
Sign up to set email alerts
|

Two-Component Redox Organocatalyst for Peptide Bond Formation

Abstract: Peptides are fundamental therapeutic modalities whose sequence-specific synthesis can be automated. Yet, modern peptide synthesis remains atom uneconomical and requires an excess of coupling agents and protected amino acids for efficient amide bond formation. We recently described the rational design of an organocatalyst that can operate on Fmoc amino acidsthe standard monomers in automated peptide synthesis (J. Am. Chem. Soc. 2019, 141, 15977). The catalytic cycle centered on the conversion of the carboxylic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 47 publications
(91 reference statements)
0
14
0
Order By: Relevance
“…Despite the length of glutaraldehyde is only 0.75 nm [ 66 ], it apparently provides a sufficient distance to prevent non-specific adsorption of the enzyme. Longer linkers, such as tetradecanedioic and docosanedioic dicarboxylic acids with approximate extended chain lengths of 1.4 and 2.2 nm, respectively, were also explored [ 67 ], however, the interaction of carboxyl group terminal linkers with amino functionalized supports (formation of a peptide bond) is less than favorable, requiring elevated temperatures or/and a catalyst [ 68 , 69 ].…”
Section: Methods Of Cellulase Immobilizationmentioning
confidence: 99%
“…Despite the length of glutaraldehyde is only 0.75 nm [ 66 ], it apparently provides a sufficient distance to prevent non-specific adsorption of the enzyme. Longer linkers, such as tetradecanedioic and docosanedioic dicarboxylic acids with approximate extended chain lengths of 1.4 and 2.2 nm, respectively, were also explored [ 67 ], however, the interaction of carboxyl group terminal linkers with amino functionalized supports (formation of a peptide bond) is less than favorable, requiring elevated temperatures or/and a catalyst [ 68 , 69 ].…”
Section: Methods Of Cellulase Immobilizationmentioning
confidence: 99%
“…[39b] In 2021, our group reported the synthesis of secondary and tertiary amines between heteroaryl halides (54) and amines under metal-, external-base-and solvent-free conditions (Scheme 11a). [39c] Using this protocol, various heteroaromatic amines and their HCl forms (55) were obtained in up to 97 % yields. Mechanistic studies via precision prediction of pK aH (amines) and selectivity experiments revealed that the acidity of both amine substrates and products played a crucial role in promoting this amination process, while the excess amounts of the amine substrates were beneficial for this transformation.…”
Section: Amination Via Organic Catalysts or Promotersmentioning
confidence: 99%
“…In 2022, Arora and co-workers reported a two-component organocatalyst for peptide bond formation (Scheme 17a). [55] A combination of a seleno-containing urea catalyst (64) and 34 * [O] was used as the catalytic system, while molecular oxygen (O 2 ) was utilized as a terminal oxidant and PhSiH 3 as a terminal reductant (Scheme 17b). With regard to the proposed catalytic cycle, the carboxylic acid ( 91) was firstly converted into the corresponding selenoester (Int-11) in situ from a diselenide catalyst (Catalyst-Se) 2 (64), which was then attacked by the amine substrate (92).…”
Section: The Catalytic Amidation Of Carboxylic Acids With Aminesmentioning
confidence: 99%
“…To streamline protein retrosynthesis and develop tools to improve CPS user access, we hypothesized that a rationally designed ambiphilic organocatalyst combining nucleophilic (e.g., thiol) ,, and electrophilic (e.g., aldehyde, iminium) , functionalities could catalyze an aqueous thioester aminolysis reaction between solid-phase peptide synthesis accessible peptide partners (Figure a) . Inspired by the mechanisms of NCL and auxiliary-based ligation reactions, ,, we envisioned an organocatalytic process to achieve Cys-independent thioacyl aminolysis between any C -terminal thioester peptide-1 and N -terminal peptide-2.…”
Section: Introductionmentioning
confidence: 99%